Random laser rn ZnO powder pumped by picosecond pulses - Nguyen, The Binh (H. : ĐHQGHN, 2017)
We report ow studies of random laser from ZnO powder at room temperature. The powder of ZnO colloidal spheres was synthesized by hydrolysis of Zinc acetate dehydrate. The random lasing around 380nm was produced from a layer of the ZnO powder pumped by the third harmonics (:SSnm) of a picosecond mode locked Nd:YAG laser (1L2143B-- Ekspla). Above a pump threshold, discrete lasing modes of random laser action with resonant feedback appeared in the emission speckum. Our experimental results show that random lasing can be produced from a layer of ZnO spherical nanoparticle powder on glass substrate.